Anne's House of Dreams - Montgomery, Lucy Maud; Lucy Maud Montgomery (Canada HarperCollins Publisher, 1972)
Anne's House of Dreams (1917) follows Anne Shirley and Gilbert Blythe's early married life as they move to a small home in Four Winds Harbor, Prince Edward Island. The story chronicles their joys, including new friendships with Captain Jim and neighbor Cornelia Bryant, alongside heartbreaking trials, specifically the loss of their first child. Amidst these personal challenges, Anne matures, supporting her neighbors and cementing her love for Gilbert, finding profound happiness in her dream life.
English
Keywords: Novel; Young adult literature